Impact of Balanced Scorecard Implementation to Employee Well-Being: Evidence from a Manufacturing Company in Vietnam - Edsel A Patal; Nguyễn Sinh Công; Trịnh Huy Ngọc; Jesus P Briones; Joanna Paula E Verano (International Journal of Entrepreneurship, Business, and Creative Economy, 2025)
Well-being of employees is important in order to provide prompt and committed production of high-quality products and services in manufacturing industries. This study investigated the relationship between balanced scorecard (BSC) implementation and employee well-being (EWB) in a manufacturing company in Vietnam. Recognizing the importance of both BSC as a strategic tool and EWB as a driver of organizational success, the researchers aimed to address the limited research directly evaluating the impact of BSC implementation on the wide range of EWB dimensions. Using a quantitative-descriptive research method, data were collected from 350 employees from a manufacturing company in Vietnam through a self-structured questionnaire formatted in HMIS scientific survey software form and distributed via electronic mail and messenger. The data were analyzed using frequency, percentage, weighted mean, and simple linear regression. The findings revealed a high level of BSC implementation and a correspondingly high level of EWB within the studied company. The findings revealed a significant positive relationship between all dimensions of BSC and the key dimensions of EWB. The study concluded that BSC implementation positively influences EWB by providing a clearer understanding of organizational strategy, increasing employees' sense of purpose, and aligning individual efforts with strategic goals. The study also proposed guidelines for BSC implementation to further enhance EWB. The study offers managers useful, evidence-based recommendation on how the use BSC can improve and maintain EWB for mutual gain of both the organization and employees.